Predicting Wife Abuse Acceptance according to Gender Stereotypes in Violated Women - Tamaddoni, Sahar; Masoudi, Shahed; Fotovvat, Akram (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study was to predict wife abuse acceptance among the women based on the gender stereotypes variable in violated women. Accordingly, the population was the women admitted to legal medicine organization during one year (2017-2018), of whom 380 women were selected for inclusion in the study using convenience sampling. They were evaluated using wife abuse questionnaire by Ghahari et al. (2006) and couples gender stereotypes by Amri (2007). Data were examined using simple regression. Graphical and systematic analysis methods were used to analyze the data. The results showed that gender stereotypes can predict wife abuse. Thus, this variable can have a significant role in wife abuse acceptance among women, and women with this scale may be more vulnerable to harm.